2019
DOI: 10.3324/haematol.2019.237396
|View full text |Cite
|
Sign up to set email alerts
|

Histone-induced thrombotic thrombocytopenic purpura in adamts13−/− zebrafish depends on von Willebrand factor

Abstract: Histone-induced thrombotic thrombocytopenic purpura in adamts13-/zebrafish depends on von Willebrand factor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 48 publications
0
36
1
Order By: Relevance
“…Also, the specific NETs components such as free histone, cfDNA, and histone/DNA complexes may activate the intrinsic and extrinsic coagulation cascade pathways and platelets while reducing tissue factor pathway inhibitor and protein C activity, leading to enhanced potential for thrombus formation 34,46 . Recent studies demonstrate that purified histone can directly trigger endothelial exocytosis, resulting in massive release of VWF from Weibel‐Palade bodies and thus thrombocytopenia in mice 52 and triggering a “TTP‐like” syndrome in ADAMTS13‐deficient zebrafish 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the specific NETs components such as free histone, cfDNA, and histone/DNA complexes may activate the intrinsic and extrinsic coagulation cascade pathways and platelets while reducing tissue factor pathway inhibitor and protein C activity, leading to enhanced potential for thrombus formation 34,46 . Recent studies demonstrate that purified histone can directly trigger endothelial exocytosis, resulting in massive release of VWF from Weibel‐Palade bodies and thus thrombocytopenia in mice 52 and triggering a “TTP‐like” syndrome in ADAMTS13‐deficient zebrafish 9 …”
Section: Discussionmentioning
confidence: 99%
“…Regardless of its etiology, severe deficiency of plasma ADAMTS13 is necessary, but often not sufficient to result in an acute episode of TTP. This was demonstrated in patients with cTTP 5 or in a murine model of TTP, [6][7][8][9][10] suggesting that additional triggers may be needed for the development of a full-blown TTP episode.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with acute TTP, elevated levels of DNA-histone complexes and MPO are detected compared to those in healthy donors, and these increased levels are inversely correlated with platelet counts, implying that DNA-histone complexes and MPO may contribute to thrombopenia (142). Zheng et al successfully established novel ADAMTS13 -/zebrafish lines that exhibited spontaneous but mild feature of TTP (143). They found that lysine-rich histone induced a more severe and persistent TTP phenotype and higher mortality rate in ADAMTS13 -/than in wild-type zebrafish, indicating that histone might trigger and aggravate TTP in individuals with severe ADAMTS13 deficiency.…”
Section: Nets Mediating Vwf and Adamts13 Activities May Form A Vicioumentioning
confidence: 99%
“…Zheng et al. successfully established novel ADAMTS 13 –/– zebrafish lines that exhibited spontaneous but mild feature of TTP ( 143 ). They found that lysine-rich histone induced a more severe and persistent TTP phenotype and higher mortality rate in ADAMTS 13 –/– than in wild-type zebrafish, indicating that histone might trigger and aggravate TTP in individuals with severe ADAMTS13 deficiency.…”
Section: The Net-vwf Axis In Immunothrombosis Provides Novel Potentiamentioning
confidence: 99%
See 1 more Smart Citation